IMPLEMENTATION OF SISTEM INFORMASI LOCAL GOVERNMENT (SIPD) IN THE PROCESS OF FINANCIAL ADMINISTRATION - Anggreani, Anne Kurry; Haliah, Haliah; Kusumawati, Andi (IJMA (Indonesian Journal of Management and Accounting), 2024)
Law no. 23 of 2014 article 391 states that Local Governments are required to provide Local Government Information. Referring to the Law, the Ministry of Home Affairs issued Permendagri Number 70 of 2019 specifically discussing Regional Government Information System (SIPD). SIPD is an information system designed to manage matters relating to Regional Development Information, Regional Financial Information, and other interconnected Regional Government Information to be utilized in the implementation of regional development. This study aims to analyze the implementation of the use of SIPD in various local government agencies. The method used in this research is literature review by collecting various literature with non-print sources in the form of e-journals and e-books. The results found that since 2024, the use of SIPD has been required in all regional apparatus organizations. However, the utilization of SIPD at the local government level is still not going well. SIPD still has several shortcomings that hinder the effectiveness of local government performance. Through this article, we will discuss how the implementation of SIPD, what are the obstacles found, and the solutions that can be provided.